Leveraging Blockchain and AI for Pharma Supply Chain Efficiency - Mohan Venkataraman (Blockchain in Healthcare Today)
The presentation discusses the potential of blockchain and AI to revolutionize the pharmaceutical supply chain. The author, with a rich history in healthcare technology, highlights the inefficiencies and challenges faced by the industry, particularly in areas like drug discovery, manufacturing, and distribution.